Theoretical analysis of interaction between radio pulses and Colorado potato beetles in the potato plant environment - Сили, Иван Иванович (Technology audit and production reserves, 2015)
To analyze the distribution of electric intensity of radio-pulse radiation in the plant environment with Colorado potato beetles it was developed the model in the form of the box filled with an isotropic dielectric medium with permittivity and conductivity. The nonstationary problem describing the distribution of electrical intensity of radio-pulse radiation by Maxwell's equations, using Laplace transform reduced to the Helmholtz equation. Solution of Helmholtz equations were obtained by separation of variables. After a series of transformations were obtained by the equation of the electric field components for the plant layer of the Colorado potato beetles. The study of the radio-pulse electromagnetic radiation distribution in the plant environment with Colorado potato beetles and their larvae will determine the necessary biotropic parameters (pulse-modulated frequency, pulse power, pulse period, pulse duration, time of exposure of the plant environment with Colorado potato beetles) radio-pulse energo-informational electromagnetic radiation to suppress reproduction ability of the beetles and destroying their larvae.